Mortality salience and its influence on individual and collective identity motives: An experimental study - Campos, Sebastián (2017)
The present investigation intends to determine mortality salience’s impact on individual and collective identity, through identity motives such as self-esteem, efficacy, belongingness, distinctiveness, continuity and meaning. It was hypothesized that the awareness of one’s own death would boost the described identity motives at both individual and collective levels. Throughout an experimental design it was found that, for individual identity, the experimental group (exposed to mortality salience) showed marginally higher punctuations than the control group for the self-esteem and distinctiveness motives and significantly higher punctuations for the continuity motive. At the collective identity level mortality salience has no effect on the identity motives.